Ophthalmic material and method for preparing contact lenses using the same
By adding methyldopa, rare earth element-tyrosine complex and menthol to the contact lens material, the shortcomings of existing contact lens materials in hydrophilicity, protein adsorption and infection resistance are solved, and higher wear comfort and eye health effects are achieved.
Patent Information
- Application Number
- CN202411155924.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-22
AI Technical Summary
Existing contact lens materials have shortcomings in hydrophilicity, protein adsorption resistance and infection resistance, and cannot meet the growing functional needs.
A new ophthalmic material was prepared by using methyldopa as an additive, combining acrylate compounds and crosslinking agents. This material improves the wetting of the lens surface through the amphoteric properties of methyldopa, reduces protein adsorption, and enhances the antibacterial and soothes eye fatigue effects through the addition of rare earth element-tyrosine complexes and menthol.
It significantly improves the hydrophilicity and anti-infection ability of contact lenses, reduces protein deposition, prevents tear film evaporation and dry eye disease, improves wear comfort, and plays a role in lowering blood pressure and soothes eye fatigue through the sustained release mechanism.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of contact lenses, in particular to an ophthalmic material and a method for preparing contact lenses by using the same. Background Art
[0002] Dopamine (DA) is a substance belonging to the catecholamine class. It is one of the important neurotransmitters in the central nervous system and an important active substance secreted by the retina. The metabolism and release of dopamine in the retina are related to many physiological activities of the visual system. In recent years, the application of dopamine in the field of contact lenses has attracted widespread attention and research.
[0003] Through dopamine coating and material modification, the hydrophilicity, resistance to protein adsorption and anti-infection of contact lenses can be improved, thereby improving the comfort and safety of the wearer. In addition, dopamine can also regulate visual function and ocular surface health, improving the visual effect of contact lenses and eye health.
[0004] Dopamine and its analogs can be used to synthesize phenolquinone polymers, which can form chelates with calcium, iron, copper and other ions in the human body and produce active oxygen, which has excellent antibacterial properties. Therefore, dopamine and its analogs have a wide range of applications, and related products can utilize the antibacterial properties of dopamine materials to improve the user's eye hygiene and safety.
[0005] However, the specific selection and research of various dopamine derivatives are still at the macro level. With the increasing functional demand for contact lenses, there is an urgent need for contact lens materials with better hydrophilicity, resistance to protein adsorption and anti-infection capabilities, as well as other effects. Summary of the invention
[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide an ophthalmic material and a method for preparing contact lenses using the same.
[0007] The above object of the present invention is achieved through the following technical solutions:
[0008] An ophthalmic material comprising the following components in percentage by weight:
[0009] Methyldopa 0.01-0.5%;
[0010] Acrylate compounds 99.1~99.5%;
[0011] Cross-linking agent 0.2~0.8%;
[0012] The molecular formula of methyldopa is:
[0013] .
[0014] In the present invention, the acrylate compound and the cross-linking agent are the main contact lens components. The present invention also uses methyldopa as an additive to add to the contact lens material, and utilizes the amphoteric properties of methyldopa, which has both carboxyl and amino groups, to more significantly increase the wettability of the contact lens surface and more effectively reduce protein adsorption, so that the lens surface can effectively retain more moisture, reduce protein deposition, prevent tear film evaporation and dry eye, and improve wearing comfort. Secondly, the methyldopa component with a fine content is transmitted to the blood vessels of the eye through sustained release, and is transmitted to the central nervous system with the blood, thereby playing a role in lowering blood pressure.
[0015] Furthermore, the crosslinking agent is selected from one or more of trimethylolpropane trimethacrylate, trihydroxypropane trimethacrylate, ethylene glycol dimethacrylate or ethylene glycol diacrylate.
[0016] Furthermore, the acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is selected from one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate or monoglyceride; and the hydrophobic monomer is selected from one or more of ethoxyethyl methacrylate, methyl methacrylate or lauryl methacrylate.
[0017] Furthermore, the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 1 to 8:1.
[0018] Furthermore, the ophthalmic material is also added with 0.001 to 0.03% by mass of a rare earth element-tyrosine complex.
[0019] Furthermore, the rare earth element is selected from one or more of europium, samarium and dysprosium.
[0020] In addition to methyldopa, the rare earth element-tyrosine complex added in the present invention has good antibacterial properties, and its presence in the contact lens is more stable, and can play a long-term antibacterial role.
[0021] Furthermore, the ophthalmic material is further added with 0.01 to 0.1% by weight of menthol and / or menthol ester.
[0022] The present invention also adds menthol and / or menthol ester to the ophthalmic material. When the tear infiltrates the contact lens, the menthol ester can slowly decompose and release menthol, and the menthol can be slowly released from the contact lens, thereby achieving a cooling and soothing effect on the eyes and reducing fatigue. Secondly, methyldopa has an amino group, which can promote the decomposition of menthol ester in the tear environment, thereby improving the release capacity of menthol, so that when the eyes have more tear secretion, the menthol ester decomposes and releases more menthol, thereby more effectively and quickly relieving eye fever and eye fatigue.
[0023] Furthermore, the menthol ester is menthyl lactate.
[0024] A method for preparing contact lenses using the above ophthalmic material comprises the following steps:
[0025] S1: Prepare the solution according to the dosage of each component;
[0026] S2: Pour the solution into a sandwich mold made of stainless steel and PTFE sheet, put it into an irradiation device or oven and react at 100°C for 24 hours to obtain a sample;
[0027] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0028] Furthermore, in the step S1, the prepared solution is first heated to 45-50° C. for 20-40 minutes.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] By using methyldopa as an additive to prepare ophthalmic materials, the hydrophilicity of contact lenses is significantly improved, protein adsorption is reduced, and anti-infection ability is enhanced, thereby improving the comfort and safety of the wearer. In addition, methyldopa can also be delivered to the blood vessels of the eye through sustained release, which has the effect of lowering blood pressure. The rare earth element-tyrosine complex further added has long-lasting antibacterial properties, and the addition of menthol and / or menthol ester can release menthol in the tear environment to achieve the effect of relieving eye fatigue. These improvements combined not only improve the material properties of contact lenses, but also provide significant improvements in wearing comfort and eye health. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with embodiments.
[0032] Example 1
[0033] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0034] Methyldopa 0.01%;
[0035] Acrylate compounds 99.49%;
[0036] Crosslinking agent 0.5%.
[0037] The molecular formula of methyldopa is:
[0038] .
[0039] The crosslinking agent is trimethylolpropane trimethacrylate.
[0040] The acrylate compound comprises a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is hydroxyethyl methacrylate and the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 6:1.
[0041] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0042] S1: Prepare the solution according to the dosage of each component;
[0043] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0044] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0045] Example 2
[0046] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0047] Methyldopa 0.5%;
[0048] Acrylate compounds 99.1%;
[0049] Crosslinking agent 0.4%.
[0050] The crosslinking agent is trimethylolpropane trimethacrylate.
[0051] The acrylate compound comprises a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is hydroxyethyl methacrylate and the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 6:1.
[0052] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0053] S1: Prepare the solution according to the dosage of each component;
[0054] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0055] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0056] Example 3
[0057] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0058] Methyldopa 0.3%;
[0059] Acrylate compound 99.5%;
[0060] Crosslinking agent 0.2%.
[0061] The crosslinking agent is trimethylolpropane trimethacrylate.
[0062] The acrylate compound comprises a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is hydroxyethyl methacrylate and the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 6:1.
[0063] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0064] S1: Prepare the solution according to the dosage of each component;
[0065] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0066] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0067] Example 4
[0068] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0069] Methyldopa 0.2%;
[0070] Acrylate compounds 99.3%;
[0071] Crosslinking agent 0.5%.
[0072] The crosslinking agent is trimethylolpropane trimethacrylate.
[0073] The acrylate compound comprises a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is hydroxyethyl methacrylate and the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 6:1.
[0074] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0075] S1: Prepare the solution according to the dosage of each component;
[0076] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0077] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0078] Example 5
[0079] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0080] Methyldopa 0.1%;
[0081] Acrylate compounds 99.1%;
[0082] Crosslinking agent 0.8%.
[0083] The crosslinking agent is trimethylolpropane trimethacrylate.
[0084] The acrylate compound comprises a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is hydroxyethyl methacrylate and the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 6:1.
[0085] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0086] S1: Prepare the solution according to the dosage of each component;
[0087] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0088] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0089] Example 6
[0090] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0091] Methyldopa 0.5%;
[0092] Acrylate compounds 99.1%;
[0093] Crosslinking agent 0.4%.
[0094] The crosslinking agent is trihydroxypropane trimethacrylate.
[0095] The acrylate compound comprises a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is hydroxyethyl acrylate and the hydrophobic monomer is selected from methyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0096] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0097] S1: Prepare the solution according to the dosage of each component;
[0098] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0099] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0100] Example 7
[0101] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0102] Methyldopa 0.3%;
[0103] Acrylate compound 99.5%;
[0104] Crosslinking agent 0.2%.
[0105] The crosslinking agent is ethylene glycol dimethacrylate.
[0106] The acrylate compound comprises a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is monoglyceride of acrylate, and the hydrophobic monomer is selected from lauryl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 6:1.
[0107] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0108] S1: Prepare the solution according to the dosage of each component;
[0109] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0110] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0111] Example 8
[0112] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0113] Methyldopa 0.2%;
[0114] Acrylate compounds 99.3%;
[0115] Crosslinking agent 0.5%.
[0116] The crosslinking agent is trimethylolpropane trimethacrylate.
[0117] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0118] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0119] S1: Prepare the solution according to the dosage of each component;
[0120] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0121] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0122] Example 9
[0123] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0124] Methyldopa 0.2%;
[0125] Acrylate compounds 99.29%;
[0126] Cross-linking agent 0.5%;
[0127] Rare earth element-tyrosine complex 0.01%.
[0128] The crosslinking agent is trimethylolpropane trimethacrylate.
[0129] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0130] Rare earth oxides are reacted with an appropriate excess of hydrochloric acid to form rare earth hydrochloride, and then the materials are added in a ratio of n(RECl3·nH2O)∶n(Tyr)=1∶3(RE=Dy). First, a certain amount of rare earth salt and tyrosine are accurately weighed and dissolved in 95% ethanol solution respectively. When tyrosine is dissolved, 1mol / L HCl is used to adjust the solution to pH=3, and then the rare earth chloride salt is mixed with the tyrosine solution, heated and stirred at 60-65℃, and refluxed. After reacting for about 3h, it is transferred to a water bath for slow evaporation and concentration, and vacuum dried to obtain a rare earth element-tyrosine complex.
[0131] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0132] S1: Prepare the solution according to the dosage of each component;
[0133] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0134] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0135] Example 10
[0136] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0137] Methyldopa 0.2%;
[0138] Acrylate compounds 99.28%;
[0139] Cross-linking agent 0.5%;
[0140] Rare earth element-tyrosine complex 0.02%.
[0141] The crosslinking agent is trimethylolpropane trimethacrylate.
[0142] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0143] Rare earth oxides are reacted with an appropriate excess of hydrochloric acid to form rare earth hydrochloride, and then the materials are added in a ratio of n(RECl3·nH2O)∶n(Tyr)=1∶3(RE=Dy). First, a certain amount of rare earth salt and tyrosine are accurately weighed and dissolved in 95% ethanol solution respectively. When tyrosine is dissolved, 1mol / L HCl is used to adjust the solution to pH=3, and then the rare earth chloride salt is mixed with the tyrosine solution, heated and stirred at 60°C for reflux, and after reacting for about 3 hours, it is transferred to a water bath for slow evaporation and concentration, and vacuum dried to obtain a rare earth element-tyrosine complex.
[0144] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0145] S1: Prepare the solution according to the dosage of each component;
[0146] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0147] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0148] Embodiment 11
[0149] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0150] Methyldopa 0.3%;
[0151] Acrylate compounds 99.27%;
[0152] Cross-linking agent 0.5%;
[0153] Rare earth element-tyrosine complex 0.03%.
[0154] The crosslinking agent is trimethylolpropane trimethacrylate.
[0155] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0156] Rare earth oxides are reacted with an appropriate excess of hydrochloric acid to form rare earth hydrochloride, and then the materials are added in a ratio of n(RECl3·nH2O)∶n(Tyr)=1∶3(RE=Dy). First, a certain amount of rare earth salt and tyrosine are accurately weighed and dissolved in 95% ethanol solution respectively. When tyrosine is dissolved, 1mol / L HCl is used to adjust the solution to pH=3, and then the rare earth chloride salt is mixed with the tyrosine solution, heated and stirred at 60-65℃, and refluxed. After reacting for about 3h, it is transferred to a water bath for slow evaporation and concentration, and vacuum dried to obtain a rare earth element-tyrosine complex.
[0157] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0158] S1: Prepare the solution according to the dosage of each component;
[0159] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0160] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0161] Example 12
[0162] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0163] Methyldopa 0.3%;
[0164] Acrylate compounds 99.27%;
[0165] Cross-linking agent 0.5%;
[0166] Menthol 0.03%.
[0167] The crosslinking agent is trimethylolpropane trimethacrylate.
[0168] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0169] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0170] S1: Prepare the solution according to the dosage of each component;
[0171] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0172] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0173] Embodiment 13
[0174] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0175] Methyldopa 0.3%;
[0176] Acrylate compounds 99.19%;
[0177] Cross-linking agent 0.5%;
[0178] Menthol 0.01%.
[0179] The crosslinking agent is trimethylolpropane trimethacrylate.
[0180] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0181] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0182] S1: Prepare the solution according to the dosage of each component;
[0183] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0184] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0185] Embodiment 14
[0186] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0187] Methyldopa 0.3%;
[0188] Acrylate compounds 99.1%;
[0189] Cross-linking agent 0.5%;
[0190] Menthol 0.1%.
[0191] The crosslinking agent is trimethylolpropane trimethacrylate.
[0192] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0193] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0194] S1: Prepare the solution according to the dosage of each component;
[0195] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0196] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0197] Embodiment 15
[0198] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0199] Methyldopa 0.3%;
[0200] Acrylate compounds 99.15%;
[0201] Cross-linking agent 0.5%;
[0202] Menthyl lactate 0.05%.
[0203] The crosslinking agent is trimethylolpropane trimethacrylate.
[0204] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0205] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0206] S1: Prepare the solution according to the dosage of each component;
[0207] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0208] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0209] Example 16
[0210] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0211] Methyldopa 0.3%;
[0212] Acrylate compounds 99.15%;
[0213] Cross-linking agent 0.5%;
[0214] Menthyl lactate 0.02%
[0215] Menthol 0.03%.
[0216] The crosslinking agent is trimethylolpropane trimethacrylate.
[0217] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0218] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0219] S1: Prepare the solution according to the dosage of each component;
[0220] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0221] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0222] Embodiment 17
[0223] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0224] Methyldopa 0.3%;
[0225] Acrylate compounds 99.15%;
[0226] Cross-linking agent 0.5%;
[0227] Menthyl lactate 0.02%
[0228] Menthol 0.03%.
[0229] The crosslinking agent is trimethylolpropane trimethacrylate.
[0230] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0231] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0232] S1: Prepare the solution according to the amount of each component, and heat the prepared solution to 45°C for 40 minutes;
[0233] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0234] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0235] Comparative Example
[0236] Comparative Example 1
[0237] An ophthalmic material disclosed in the present invention comprises the following components in percentage by mass:
[0238] Acrylate compounds 99.55%;
[0239] Cross-linking agent 0.5%;
[0240] The crosslinking agent is trimethylolpropane trimethacrylate.
[0241] The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is a mixture of hydroxyethyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1; the hydrophobic monomer is selected from ethoxyethyl methacrylate, and the mass ratio between the hydrophilic monomer and the hydrophobic monomer is 8:1.
[0242] A method for preparing contact lenses from ophthalmic materials, comprising the following steps:
[0243] S1: Prepare the solution according to the dosage of each component;
[0244] S2: The solution was poured into a sandwich mold made of stainless steel and polytetrafluoroethylene sheets. The sandwich mold reservoir cavity was 10×0.3×5 cm. The sample was placed in an oven at 100°C for 24 hours.
[0245] S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
[0246] Detection Methods
[0247] 1. Tensile performance test: The tensile testing machine is Langshan LPS-20T, elongation at break at 35°C; the sample needs to be cut into rectangular strips of 0.3cm*1cm*10cm before testing the tensile performance;
[0248] 2. Refractive index test: Refractometer: ATAGODR-M2, refractive index at 35 degrees;
[0249] 3. Moisture content test: balance Mettler MS-TS and oven DHG101-3A; the moisture content is measured by weight loss method, and the weight difference between 105°C for 24 hours and 65°C for 48 hours is calculated;
[0250] 4. Place the contact lenses in simulated tears, take out the lenses at certain intervals, measure the concentrations of methyldopa and menthol in the solution by UV spectrophotometer, and calculate the cumulative release of methyldopa and menthol after 48 hours. The results are shown in Table 2.
[0251] 5. The contact lenses prepared using the ophthalmic materials of Example 1 and Comparative Example 1 were evaluated for lubricity, comfort, coolness, and moistness using the VAS method (Visual Analogue Scale) immediately after wearing the contact lenses and 30 minutes and 1 hour after wearing them. The average score of 3 people (6 eyes) was calculated for each evaluation item. The results are shown in Table 3.
[0252]
[0253]
[0254]
[0255] Conclusion: The above tests show that the ophthalmic material prepared by the present invention and the contact lenses made of the ophthalmic material have greatly improved comfort and cool feeling. Secondly, the sustained release verification of methyldopa and menthol shows that the ophthalmic material has a long-lasting and effective release effect.
[0256] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. An ophthalmic material, characterized in that: The following components are included in mass percentage: Methyldopa 0.01-0.5%; Acrylate compounds 99.1~99.5%; Cross-linking agent 0.2~0.8%; The molecular formula of methyldopa is: The ophthalmic material further contains 0.01 to 0.1% by weight of menthol and menthol ester.
2. An ophthalmic material according to claim 1, characterized in that: The crosslinking agent is selected from one or more of trimethylolpropane trimethacrylate, trihydroxypropane trimethacrylate, ethylene glycol dimethacrylate or ethylene glycol diacrylate.
3. An ophthalmic material according to claim 1, characterized in that: The acrylate compound includes a hydrophilic monomer and a hydrophobic monomer, wherein the hydrophilic monomer is selected from one or more of hydroxyethyl methacrylate, hydroxyethyl acrylate or monoglyceride acrylate; and the hydrophobic monomer is selected from one or more of ethoxyethyl methacrylate, methyl methacrylate or lauryl methacrylate.
4. An ophthalmic material according to claim 3, characterized in that: The mass ratio between the hydrophilic monomer and the hydrophobic monomer is 1 to 8:
1.
5. An ophthalmic material according to claim 1, characterized in that: The ophthalmic material is also added with 0.001 to 0.03% by mass of a rare earth element-tyrosine complex.
6. An ophthalmic material according to claim 5, characterized in that: The rare earth element is selected from one or more of europium, samarium and dysprosium.
7. An ophthalmic material according to claim 1, characterized in that: The menthol ester is menthyl lactate.
8. A method for preparing contact lenses using the ophthalmic material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Prepare the solution according to the dosage of each component; S2: Pour the solution into a sandwich mold made of stainless steel and PTFE sheet, put it into an irradiation device or oven and react at 100°C for 24 hours to obtain a sample; S3: Immerse the sample and its mold in water, place it in a 65℃ water bath for 48 hours, change the water every 12 hours, and then demould.
9. A method for preparing a contact lens according to claim 8, characterized in that: In the step S1, the prepared solution is first heated to 45-50° C. for 20-40 minutes.
Citation Information
Patent Citations
Ophthalmic materials for implantable contact lenses
CN118165170A
Contact lens with sustained release property
US20220202610A1